ORGANIZATION OF ROAD FLOW OF TRAFFIC (Perner's Contacts, 2008)
The paper describe to the transaction study organization of road flow in the field porter's lodge No. 2 in plant Železárny a drátovny Bohumín, a.s., with a view to solving current data deficienty transmission hereof transport junction. In the paper is short described contemporary state and presented personal proposal solution of the establishment on-highway flow.
Keywords: Organization highway travel; interplant handling; logistic; logistics